LEARNER ERRORS IN WRITING DESCRIPTIVE TEXT MADE BY STUDENTS OF SMP AL ISLAM KARTASURA - Dinar Rizky Amalia (Jurnal Penelitian Humaniora, 2016)
The study aims at describing the learners’ error made by eighth grade students of SMP AL Islam Kartasura in their writing descriptive text; identifying the types of lexical error, syntactical errors, and discourse errors; explaining the frequency of each typeof errors; describing the dominant type of errors; and identifying the sources of error. The type of this research is descriptive qualitative research. In collecting the data, the writer uses elicitation and documentation technique. There are some steps ofcollecting the data; asking the students to write descriptive text, collecting the data in form of erroneous sentences and paragraph, identifying the composition, marking the types of error, and at last, listing the erroneous sentences and classifying them into the classification of errors. The collected data are analyzed using Dulay, Burt and Krashen classification of errors theory, frequency of each type of error using Slamet’s theory, and Brown’s theory for sources of error. The results of the research show that the eighth grade students of SMP AL Islam Kartasura make 291 errors in their composition which are classified into three categories of error based on the combination of linguistic category and surface strategy taxonomy. There are lexical errors that cover: misspelling 12,37% and literal translation (the use of Indonesian construction) 6,87%. Syntactical error consist of omission of {-s} as plural marker 4,12%, omission of {-s} as third singular person marker 10,31%, misselection of have instead of has 8,25%, the use of verb-ing in structure phrase 1,72%, omission of verb 2,40%, omission of be 1,5%, addition of be 2,40%, the use of prepositionin prepositional phrase 3,44%, omission of article 1,37%, addition of the article 1,72%, misordering in noun phrase 19,93%, misordering in phrase 1,37%, and the last is addition of unnecessary word 5,50%. Discourse errors is 2,06% that covercomponent of discourse in reference 2,06%. The writer also finds 2 dominant sources of errors, namely interlingual transfer and intralingual transfer.